3D constraints on a possible deep > 2.5 km massive sulphide mineralization from 2D crooked-line seismic reflection data in the Kristineberg mining area, northern Sweden - Malehmir, A.; Schmelzbach, C.; Bongajum, E.; Bellefleur, G.; Juhlin, Christopher; Tryggvason, A. (Elsevier BV, 2009)
2D crooked-line seismic reflection surveys in crystalline environments are often considered challenging in their processing and interpretation. These challenges are more evident when complex diffraction signals that can originate from out-of-the-plane and a variety of geological features are present. A seismic profile in the Kristineberg mining area in northern Sweden shows an impressive diffraction package, covering an area larger than 25 km2 in the subsurface at depths greater than 2.5 km. We present here a series of scenarios in which each can, to some extent, explain the nature of this extraordinarily large package of diffractions. Cross-dip analysis, diffraction imaging and modeling, as well as 3D processing of the crooked-line data provided constraints on the interpretation of the diffraction package. Overall, the results indicate that the diffraction package can be associated with at least four main short south-dipping diffractors in a depth range of 2.5-4.5 km. Candidate scenarios for the origin of the diffraction package are: (1) a series of massive sulphide deposits, (2) a series of mafic-ultramafic intrusions, (3) a major shear-zone and (4) multiple contact lithologies. We have also investigated the possible contribution of mode-converted scattered energy in the diffraction package using a modified converted-wave 3D prestack depth migration algorithm with the results indicating that a majority of the diffractions are P-wave diffractions. The 3D prestack migration of the data provided improved images of a series of steeply north-dipping mafic-ultramafic sill intrusions to a depth of about 4 km, where the diffractions appear to focus after the migration. The results and associated interpretations presented in this paper have improved our understanding of this conspicuous package of diffractions and may lead to re-evaluation of the 3D geological model of the Kristineberg mining area. © 2009 Elsevier B.V. All rights reserved.